Fluorescence Characteristics of Chromophoric Dissolved Organic Matter in the Eastern Indian Ocean: A Case Study of Three Subregions - Liu, Yang; Sun, Jun; Wang, Xingzhou; Liu, Xiaofang; Wu, Xi; Chen, Zhuo; Gu, Ting; Wang, Weiqiang; Yu, Linghui; Guo, Yu; Wen, Yujian; Zhang, Guodong; et al. (Frontiers in Marine Science, 2021)
Comprising one of the major carbon pools on Earth, marine dissolved organic matter (DOM) plays an essential role in global carbon dynamics. The objective of this study was to better characterize DOM in the eastern Indian Ocean. To better understand the underlying mechanisms, seawater samples were collected in October and November of 2020 from sampling stations in three subregions: the mouth of the Bay of Bengal, Southern Sri Lanka, and Western Sumatra. We calculated and evaluated different hydrological parameters and organic carbon concentrations. In addition, we used excitation emission matrix (EEM) spectroscopy combined with parallel factor analysis (PARAFAC) to analyze the natural water samples directly. Parameters associated with chromophoric DOM did not behave conservatively in the study areas as a result of biogeochemical processes. We further evaluated the sources and processing of DOM in the eastern Indian Ocean by determining four fluorescence indices (the fluorescence index, the biological index, the humification index, and the freshness index β/α). Based on EEM-PARAFAC, we identified six components (five fluorophores) using the peak picking technique. Commonly occurring fluorophores were present within the sample set: peak A (humic-like), peak B (protein-like), peak C (humic-like), and peak T (tryptophan-like). The fluorescence intensity levels of the protein-like components (peaks B and T) were highest in the surface ocean and decreased with depth. In contrast, the ratio of the two humic-like components (peaks A and C) remained in a relatively narrow range in the bathypelagic layer compared to the surface layer, which indicates a relatively constant composition of humic-like fluorophores in the deep layer.